Mineralocorticoid Receptor in Myeloid Cells Mediates Angiotensin II-Induced Vascular Dysfunction in Female Mice - Manrique-Acevedo, Camila; Padilla, Jaume; Naz, Huma; Woodford, Makenzie L.; Ghiarone, Thaysa; Aroor, Annayya R.; Hulse, Jack L.; Cabral-Amador, Francisco J.; Martinez-Diaz, Vanesa; Hans, Chetan P.; Whaley-Connell, Adam; Martinez-Lemus, Luis A.; et al. (Frontiers in Physiology, 2021)
Enhanced mineralocorticoid receptor (MR) signaling is critical to the development of endothelial dysfunction and arterial stiffening. However, there is a lack of knowledge about the role of MR-induced adipose tissue inflammation in the genesis of vascular dysfunction in women. In this study, we hypothesize that MR activation in myeloid cells contributes to Angiotensin II (Ang II)-induced aortic stiffening and endothelial dysfunction in females via increased pro-inflammatory (M1) macrophage polarization. Female mice lacking MR receptor in myeloid cells (MyMRKO) were infused with Ang II (500 ng/kg/min) for 4 weeks. This was followed by determinations of aortic stiffness and vasomotor responses, as well as measurements of markers of inflammation and macrophage infiltration/polarization in different adipose tissue compartments. MyMRKO mice were protected against Ang II-induced aortic endothelial stiffening, assessed via atomic force microscopy in aortic explants, and vasorelaxation dysfunction, measured by aortic wire-myography. In alignment, MyMRKO mice were protected against Ang II-induced macrophage infiltration and M1 polarization in visceral adipose tissue (VAT) and thoracic perivascular adipose tissue (tPVAT). Collectively, this study demonstrates a critical role of MR activation in myeloid cells in the pathogenesis of vascular dysfunction in females associated with pro-inflammatory macrophage polarization in VAT and tPVAT. Our data have potential clinical implications for the prevention and management of cardiovascular disease in women, who are disproportionally at higher risk for poor outcomes.